The effect of nitrogen alloying on hydrogen-assisted plastic deformation and fracture in FeMnNiCoCr high-entropy alloys. (15th March 2021) - Astafurova, E.G.; Panchenko, M.Yu.; Reunova, K.A.; Mikhno, A.S.; Moskvina, V.A.; Melnikov, E.V.; Astafurov, S.V.; Maier, H.J.
Abstract: In the present study, the effect of nitrogen alloying on hydrogen embrittlement in FeMnNiCoCr high-entropy alloys was investigated. In tension, hydrogen-free nitrogen-alloyed FeMnNiCoCrN alloy (0.37 wt.% N) demonstrated higher strength, strain hardening, and elongation-to-failure than the interstitial-free FeMnNiCoCr Cantor alloy. Despite the different tensile properties, both alloys fractured via a ductile dimple micromechanism. After hydrogen charging, the nitrogen-alloyed material demonstrated lower strain hardening and higher sensitivity to hydrogen-assisted embrittlement than the interstitial-free alloy. Both alloys featured a stable austenitic structure and similar grain size, yet, the nitrogen-alloyed FeMnNiCoCr alloy was more susceptible to hydrogen embrittlement. Although, the overall degradation effects appear similar, there are pronounced differences in mechanical behavior and hydrogen transport upon hydrogen charging when the high-entropy alloys are compared to conventional austenitic stainless steels, and the experiments reveales that nitrogen alloying enhances hydrogen diffusivity in the Cantor alloy. Graphical abstract: Image, graphical abstract